Two thousand years in Dendi, northern Benin : archaeology, history and memory - Haour, Anne, (Journal of African Archaeology Monograph Series, 2018)
In Two Thousand Years in Dendi, Northern Benin an international team examines a little-known part of the Niger River valley, West Africa, over the longue durée. This area, known as Dendi, has often been portrayed as the crossroads of major West African medieval empires but this understanding has been based on a small number of very patchy historical sources. Working from the ground up, from the archaeological sites, standing remains, oral traditions and craft industries of Dendi, Haour and her team offer the first in-depth account of the area. Contributors are: Paul Adderley, Mardjoua Barpougouni, Victor Brunfaut, Louis Champion, Annalisa Christie, Barbara Eichhorn, Anne Filippini, Dorian Fuller, Olivier Gosselain, David Kay, Nadia Khalaf, Nestor Labiyi, Raoul Laibi, Richard Lee, Veerle Linseele, Alexandre Livingstone Smith, Carlos Magnavita, Sonja Magnavita, Didier N'Dah, Nicolas Nikis, Sam Nixon, Franck N'Po Takpara, Jean-François Pinet, Ronika Power, Caroline Robion-Brunner, Lucie Smolderen, Abubakar Sule Sani, Romuald Tchibozo, Jennifer Wexler, Wim Wouters.